ANALISIS SOSIAL EKONOMI DALAM PEMANFAATAN JKN UNTUK RAWAT INAP DI YOGYAKARTA - Irene Tenriana Kenia (Jurnal Medika Hutama, 2022)
The beginning of 2014 was the initial momentum for the implementation of the National Health Insurance (JKN) organized by the Health Social Security Administration (BPJS). On the island of Java, the growth of health care facilities and hospitals is increasing. Residents on the island of Java work in the formal sector so that they have poor health and increase the tendency to seek treatment at the hospital, even hospitalize. The purpose of this study was to determine the socio-economic factors that influence the use of JKN for hospitalization in Yogyakarta. This study uses secondary data, namely the National Socio-Economic Survey (Susenas) in 2020. The research respondents were 12,466 heads of households in Yogyakarta Province. The method used in this study is Binary Regression, namely the logit and probit models. The results of the study found that the factors of age, education, and occupation, had a significant effect on the utilization of JKN. The p-value for all variables is 0.000 (p-value <0.05). Socio-economic factors that influence the use of JKN in Yogyakarta are age, education, and occupation